EXPLORING THE EFFECTIVENESS OF USING QUIZLET ON LEARNING DENTAL TERMINOLOGY: Received: 30 September 2023; Revised: 14th November 2023, 10th December 2023; Accepted: 12th December 2023 - Liang, Shu-Chuan (PEOPLE: International Journal of Social Sciences, 2024)
The main goal of this study is to evaluate the effectiveness of the Quizlet flashcard app for learning English dental terminology. 100 dental-technology students from a five-year junior college in southern Taiwan participated in this study. Participants had access to Quizlet for learning281 dental terms. By using a quasi-experimental research design, data were collected from vocabulary quizzes and a questionnaire. Vocabulary quiz results were compared to measure the effectiveness of Quizlet’s assistance. The questionnaire was distributed after the use of Quizlet to evaluate satisfactory features of the software. Preliminary research findings have shown a positive correlation between frequency of Quizlet use and the acquisition of dental vocabulary, at a significance level of p < .001~.005. In addition, the participants gave positive feedback on Quizlet’s functions with mean scores ranging from 4.71~5.0 (on a 6-point scale). Unexpectedly, the perceived benefits of using Quizlet did not result in satisfactory test scores because the students did not use it extensively. Future research can focus on the correlation between students' perceptions of educational apps and their eagerness to use them.